Impact of GFR Stratification on Tc-99m DTPA Dose Distribution in Target and Non-Target Organs: A MIRD-Based Comparative Study in Renogram Imaging - Luthfia Qalby; Wahyu Setia Budi; Eko Hidayanto (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Renogram using Technetium-99m Diethylene Triamine Pentaacetic Acid (Tc-99m DTPA) is applied to evaluate renal perfusion, glomerular filtration rate (GFR), and urinary excretion. In patients with impaired renal function, delayed tracer elimination may increase accumulation in non-target organs such as the heart and liver, resulting in greater radiation exposure and reduced image quality. Studies examining the relationship between renal function and Tc-99m DTPA dose distribution remain limited, particularly in clinical settings in Indonesia. Therefore, in this study, an organ-level quantitative analysis of Tc-99m DTPA radiopharmaceutical dose distribution and absorbed dose using the Medical Internal Radiation Dose (MIRD) approach based on Single Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) imaging was performed.METHODS: Thirty adult patients undergoing renogram were categorized into low-GFR (<60 mL/min/1.73 m²) and high-GFR (≥60 mL/min/1.73 m²) groups. Each patient received 4–5 mCi of Tc-99m DTPA intravenously. Organ activities were obtained from regions of interest (ROIs) on SPECT/CT images, and organ-level absorbed doses (mGy) were calculated using the MIRD formalism.RESULTS: In the low-GFR group, tracer retention in non-target organs increased, with absorbed doses up to twofold higher in the heart (0.0002–0.0136 mGy) and liver (0.0010–0.0178 mGy) compared to the high-GFR group. Renal absorbed doses ranged from 0.0001–0.0694 mGy, showing no significant difference between the left and right kidneys, while significant differences were observed in the heart and liver.CONCLUSION: GFR significantly affects the radiopharmaceutical dose distribution and absorbed dose of Tc-99m DTPA. Reduced renal function increases radiation exposure in non-target organs, whereas normal function results in a more localized renal dose distribution.KEYWORDS: Tc-99m DTPA, renogram, MIRD, glomerular filtration rate, absorbed dose, SPECT/CT, nuclear medicine